The Nature of Tolerance in the Frame of Christian Faith as a Contribution to Building the Unity of the Nation - Arifianto, Yonatan Alex; Saptorini, Sari; Triposa, Reni (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
Intolerant attitudes and actions that result in horizontal conflicts are inevitable in the life of a pluralistic nation like Indonesia. They hinder, however, the development of the nation's integrity protected and fought for decades by its founding fathers. Through this paper, Indonesian Christians are expected to be aware of the importance of their nation's integrity and of them living in harmony, which will bring peace. This study used a descriptive qualitative method with a literature study approach. It concluded that a correct understanding of the nature of tolerance within the framework of the Christian faith is necessary to contribute to building national unity. The tolerance possessed by Christians will maximize their role in contributing to practical building of national unity in daily life, such as in carrying out activities that emphasize coexistence and mutual respect as the realization of obedience to God's word. Christians also need to participate in inter-religious dialogue to find solutions to the problem of disintegration. Thus, the role of Christians in building national unity and integrity through tolerance has an impact on the harmony, security, and sustainability of the state.